2013
DOI: 10.1366/12-06703
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Resolved Multilayer Pigment Identification in Paintings: Combined Use of Laser-Induced Breakdown Spectroscopy (LIBS) and Optical Coherence Tomography (OCT)

Abstract: A detailed feasibility study on the combined use of laser-induced breakdown spectroscopy with optical coherence tomography (LIBS/OCT), aiming at a realistic depth-resolved elemental analysis of multilayer stratigraphies in paintings, is presented. Merging a high spectral resolution LIBS system with a high spatial resolution spectral OCT instrument significantly enhances the quality and accuracy of stratigraphic analysis. First, OCT mapping is employed prior to LIBS analysis in order to assist the selection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…In a feasibility study, this combination was suggested for use in depthresolved multi-layer pigment identification in paintings [95]. An OCT scan can provide high-resolution 3D images of the layers in the paintings, and can assist LIBS in depth-resolved elemental-composition studies by accurately measuring ablation-crater depths and ablation rates.…”
Section: Other Combinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a feasibility study, this combination was suggested for use in depthresolved multi-layer pigment identification in paintings [95]. An OCT scan can provide high-resolution 3D images of the layers in the paintings, and can assist LIBS in depth-resolved elemental-composition studies by accurately measuring ablation-crater depths and ablation rates.…”
Section: Other Combinationsmentioning
confidence: 99%
“…Novel tandem instruments, for example Raman-LIBS, have also found well-suited applications in this field, as already alluded to in the instrumental section of this review. A recent example of this trend is the state-of-the-art combined instrument incorporating optical-coherence tomography and LIBS (OCT-LIBS) [95], which was specifically constructed to aid multilayer pigment identification in paintings. This instrument enables the fast, high-resolution, nondestructive visualization of stratigraphy in paintings and makes depth-profiling substantially more precise.…”
Section: Archeological and Cultural-heritage Applicationsmentioning
confidence: 99%
“…E arly diagnosis in health care is desirable and necessary since it implies a better patient prognosis. Imaging methods are widely used in diagnostic medicine, as reviewed by Dhawan et al 1 Among the diversity of imaging modalities, optical coherence tomography (OCT), first introduced by Huang et al, 2 is now commercially available and considered the most innovative imaging technique used in ophthalmology; 3 it is also used in several other clinical applications such as dermatology, 4,5 gastroenterology, 6 cardiology, 7 gynecology, 8 oncology, 9 dentistry, 10,11 and non-medical applications, for instance, painting 12 and evaluation of materials' porosity. 13 In dentistry, OCT studies in hard and soft tissues have been performed since 1998, 10 and they have been proposed to be an effective tool to evaluate early caries and caries-related issues [14][15][16][17][18][19] and oral cancer.…”
mentioning
confidence: 99%
“…The potential to eliminate the need for polishing can thus avoid problems during the polishing process, such as cross-contamination between paint layers, or with sand particles [18]. We also note that under a more stringent experimental geometry, it may be possible to employ laser induced breakdown spectroscopy (LIBS) while making the cut, in order to gain more information about the sample [19]. …”
Section: Resultsmentioning
confidence: 99%